Turkey, Egypt, and Syria : a travelogue - Shiblī Nuʻmānī, 1857-1914 (Middle East literature in translation., 2020)
"Safarnāmah-i Rūm o Miṣr o Shām: A travelogue of Turkey, Egypt, and Syria (1894) by Shiblı̄ Numāni (1857-1914) records the experiences of a prominent Indo-Muslim historian of Islam and scholar of Arabic and Persian literatures while in the Ottoman Empire and Egypt in 1892. The resulting travelogue is a rich account of Shiblı̄'s experiences, and a social history of intellectual culture and education in Turkey, Egypt, and Syria at the end of the 19th century. Extensive annotations and explanatory material from the translator provide the reader with social, political, and historical context"--